Policies of Resilience in the New Institutional Process. The Case-Studies of Palermo and Siracusa in the South of Italy. - Trapani, Ferdinando; Minozzi, Luigi (TeMA - Journal of Land Use, Mobility and Environment, 2015)
At the end of 2012, the PON METRO National Scheme was set up in Italy, inspired by the EU Urban Agenda. It also allows towns like Palermo to test and reach targets of urban resilience, focusing on mobility and sustainable energy in order to improve life in the cities together with innovative policies of social inclusion. Other medium-sized cities also tried to face the problem of urban resilience without using national funds. The city of Siracusa, for example, made use of EU direct co-financing schemes. This paper aims to analyse the planning projects and measures adopted in Sicily over the past few years in order to examine government approaches focusing on resilience or those that are somehow linked to it. The comparison shows that, despite the wide range of opportunities (European, National and Regional policies, etc.) a number of differences may be listed in the adoption of schemes for urban planning and for the implementation of transition measures from a linear, rational, sequential, normative and regulative approach to the circular, active, flexible and versatile approach needed to tackle the problems linked to urban resilience. This proposal suggests that new policies are needed. The new policies should focus not only on funds but also on the creation of an innovative laboratory of projects involving all the cities in equal ways and on the building of a platform to exchange data and compare the different practices adopted in relation to urban and local resilience.